CHARACTERISTICS OF NATA DE SOURSOP ON THE CONCENTRATION VARIATIONS OF LIME JUICE AND MUNG BEAN EXTRACT - Helmiyana, Restu; Suryani, Titik (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Nata is one of the functional foods resulting from fermentation on the growth of Acetobacter xylinum as a source of probiotics for digestion and is beneficial for health. Soursop fruit as an innovation of nata substrate contains carbohydrates, protein, fat, calcium, phosphorus and vitamin C. The study aimed was to determine the characteristics (fiber content, reducing sugar and organoleptic quality) of nata de soursop on the variations of juice lime concentration and mung bean extract. This research method was an experiment with a Completely Randomized Design (CRD), two factors. The first factor : lime juice concentration of 1.2% and 2.8%. The second factor: mung bean extract concentration of 20% and 25%. The results of statistics showed (p > 0.05), (Asymp. sig) 0.199 > 0.05 and mung bean extract 0.078 > 0.05, so H0 was accepted that lime juice and mung bean extract were not significant on the fiber content and reducing sugar content of nata de soursop.It was concluded that the best characteristics of nata soursop were the fiber content, and the reducing sugar 4.51% and 12.7% respectively, as well the organoleptic quality of cloudy white color, chewy texture, quite sour aroma and good acceptability at the J2K1 (Lime juice 2.8% + mung bean extract 20%).